The Potential Of Dki Jakarta Tourism Object Development Case Study In Pancasila Sakti Monument In Lubang Buaya Jakarta - Nur Fitri Rahmawati; Anita Maulina; Bisma Widyawan; Trie Andari Ratna Widyastuti (Yayasan Ilomata, 2020)
The Pancasila Sakti Monument in Lubang Buaya, Jakarta is one of the tourism identities of DKI Jakarta, many efforts have been made in developing the preservation and preserving the cultural assets that are still left in the Pancasila Sakti Monument in Lubang Buaya. The purpose of this research is to determine the potential development of tourism objects in Pancasila Sakti Monument in Lubang Buaya by analyzing the historical values ​​and uniqueness. This study used a descriptive qualitative method that describes the information of the Tourism Object from the Pancasila Sakti Monument in Lubang Buaya. Data collection techniques used were interviews, literature study, observation, and documentation. The data collection was analyzed and grouped based on the research problems. The results of this study indicate that the Tourism Object namely Pancasila Sakti Monument in Lubang Buaya is one of the tourism objects that have the potential to be developed in DKI Jakarta.